2009
DOI: 10.1016/j.prostaglandins.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the prostaglandin pathway during development of invasive bladder cancer in mice

Abstract: Prostaglandin E 2 (PGE 2 ) is reported to play an important role in tumor development. We explored the differential expression of genes governing production of, and response to, PGE 2 during development of invasive bladder cancer. N-butyl-N-(4-hydroxybutyl)-nitrosamine (BBN) or vehicletreated mice (n = 4-5) were euthanized after 4-8 weeks (period 1, P1), 12-16 weeks (P2), and 20-23 weeks (P3). Half of each bladder was analyzed histologically and the other half extracted for mRNA analysis by quantitative real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…The elevated expression of COX-2 and cPLA2, as well as the reduced expression of PGDH, which might increase the production of PGE 2 , have been observed in the pathogenesis of either BBN-initiated or calculus-induced bladder cancer [19,20]. Overexpression of COX-2, a crucial rate-limiting enzyme in PGE 2 biosynthesis, has been reported both in human invasive bladder carcinoma and in carcinogen-induced bladder cancer animal models, respectively [15,17], and inhibition of COX-2 is the most common approach to inhibiting the prostaglandin pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The elevated expression of COX-2 and cPLA2, as well as the reduced expression of PGDH, which might increase the production of PGE 2 , have been observed in the pathogenesis of either BBN-initiated or calculus-induced bladder cancer [19,20]. Overexpression of COX-2, a crucial rate-limiting enzyme in PGE 2 biosynthesis, has been reported both in human invasive bladder carcinoma and in carcinogen-induced bladder cancer animal models, respectively [15,17], and inhibition of COX-2 is the most common approach to inhibiting the prostaglandin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PGDH, which degrades PGE 2 , has been shown to regulate bladder cancer progression. It is well documented that loss of PGDH expression correlates with tumor stage in bladder cancer [33], and a reduced level of PGDH and an increased expression of COX-2 have been noted in the development of bladder carcinogenesis in mice [19], and inhibition of PGDH expression in well-differentiated RT4 cells using small inhibitory RNA or short hairpin RNA has resulted in a lack of E-cadherin assembly and a more aggressive phenotype with increased motility and anchorage-independent growth [34,35]. In line with the previous findings, in our study a reduced expression of PGDH was observed in BBN-induced rat bladder carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a study of mouse bladder cancer chemical carcinogenesis showed that COX2 expression was increased while PGDH levels reduced as bladder cancers developed. 17 Work from our laboratory showed that small inhibitory RNA (siRNA) inhibition of PGDH expression in the well-differentiated RT4 human bladder cancer cell line disrupts E-cadherin complex assembly. 18 Thus, a more detailed study of PGDH expression in bladder cancer is warranted.…”
mentioning
confidence: 99%